Static Black Hole Uniqueness for nonpositive masses. (July 2022) - Borghini, Stefano
Abstract: In a renowned paper, Lee and Neves proved a Penrose inequality for spacetimes with negative cosmological constant and nonpositive mass aspect. As an application, they were able to obtain a static uniqueness theorem for Kottler spacetimes with nonpositive mass. In this paper, we propose an alternative more elementary proof of this static uniqueness result and we discuss some possible generalizations, most notably to degenerate horizons.